China and international dispute resolution in the context of the 'Belt and Road Initiative' / edited by Wenhua Shan, Sheng Zhang, Jinyuan Su. - Shan, Wenhua; Zhang, Sheng; Su, Jinyuan (Law teacher) (Cambridge University Press, 2020)
Written by eminent international judges, scholars and practitioners, this book offers a timely study of China's role in international dispute resolution in the context of the construction of the 'Belt and Road Initiative' (BRI). It provides in-depth analysis of the law and practice in the fields of international trade, commerce, investment and international law of the sea, as they relate to the BRI construction. It is the first comprehensive assessment of China's policy and practice in international dispute resolution, in general and in individual fields, in the context of the BRI construction. This book will be an indispensable reading for scholars and practitioners with interest in China and international dispute resolution. It also constitutes an invaluable reference for anyone interested in the changing international law and order, in which China is playing an increasingly significant role, particularly through the BRI construction.